2005
DOI: 10.1111/j.1075-122x.2005.21684.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Duct Ectasia

Abstract: Duct ectasia consists of dilation of the mammary ducts and is clinically manifested as nipple discharge, which is more commonly multiductal, bilateral, and colored. To identify clinical factors that might be related to duct ectasia. A case-control study was carried out on a population of 150 patients divided into two groups. Group 1 (the experimental group) comprised 100 patients with multiductal, bilateral, and colored nipple discharge, clinically representing the nipple secretion of duct ectasia. Group 2 (th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 8 publications
1
28
1
2
Order By: Relevance
“…Amongst these, 11 (33.3 %) patients were of fibroadenosis, 07 (21.2 %) patients were of mastitis, 04 (12%) patients were of fibroadenoma, 06 (18 %) patients were of breast abscess and 02 (6 % 12 In the present study, fibroadenosis was the most common benign breast disorder affecting women between 21 to 49 years age and accounted for 37 (46.2 %) cases. Similar findings were observed by Furlong AJ et al, Dixon JM et al and Rahal RMS et al in 1994, 1996and 2005 respectively, wherein they found approximately 50% women diagnosed with fibroadenosis. 13,14,15. In the present study, 03 (3.75 %) patients presented with nipple discharge and were diagnosed as cases of duct ectasia.…”
Section: Discussionsupporting
confidence: 87%
“…Amongst these, 11 (33.3 %) patients were of fibroadenosis, 07 (21.2 %) patients were of mastitis, 04 (12%) patients were of fibroadenoma, 06 (18 %) patients were of breast abscess and 02 (6 % 12 In the present study, fibroadenosis was the most common benign breast disorder affecting women between 21 to 49 years age and accounted for 37 (46.2 %) cases. Similar findings were observed by Furlong AJ et al, Dixon JM et al and Rahal RMS et al in 1994, 1996and 2005 respectively, wherein they found approximately 50% women diagnosed with fibroadenosis. 13,14,15. In the present study, 03 (3.75 %) patients presented with nipple discharge and were diagnosed as cases of duct ectasia.…”
Section: Discussionsupporting
confidence: 87%
“…Smoking has been implicated as an etiological factor in mammary duct ectasia. 24,25 No relationship of smoking and duct ectasia was seen in our study.…”
Section: Discussioncontrasting
confidence: 55%
“…The pathogenesis and the etiology of the disease are still being debated. Smoking has been implicated as an etiologic factor in mammary duct ectasia [35,36]. This association appears to be more important in young women who smoke [37].…”
Section: Mammary Duct Ectasiamentioning
confidence: 99%